Omron NX-Series programmable logic controllers - from zero to hero - Nordin, Nurdiana (Penerbit UTeM Press, 2024)
This book will provide you with a thorough foundation in PLC programming with Sysmac Studio, whether you are an enthusiast looking to expand your repertory or a rookie learner exploring the world of industrial automation. We will start with the basics, supposing you know nothing about PLCS or programming. Afterwards, we will gradually deepen your understanding by providing clear explanations, real-life examples, and engaging exercises.